ANALYSIS OF WATER MOVEMENT MANAGEMENT FOR WATER COOLING RESERVOIRS AT NUCLEAR POWER PLANTS - F. D. Pryshnicov; N. V. Beyner; H. S. Beyner (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The paper contains an analysis for efficiency of water cooling reservoirs depending on their geometrical configuration (shape) and specific features concerning management of circulating water movement while using visual graphic material.